Pengaruh Literasi Keuangan, Gaya Hidup Hedonisme dan Financial Distress Terhadap Perilaku Keuangan Mahasiswa Akuntansi - Nurul_Fajrina; Sofyan Syamsuddin; Nispa Sari (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to examine the effect of financial literacy, hedonic lifestyle, and financial distress on the financial behavior of accounting students at the University Muhammadiyah Palopo. Students often face challenges in managing personal finances, especially when consumerist lifestyles and financial pressure become dominant factors. This study uses a quantitative approach by distributing quetionnaires to 53 students as respondents, selected through purposive sampling technique. Data analysis is conducted using descriptive statistic tests, classical assumption tests, and hypothesis testing through IBM SPSS Statistic software version 27. The finding indicate that financial literacy, hedonic lifestyle, an financial distress positively contribute to students’ financial behavior. These findings highlight the importance of financial literacy, hedonic lifestyle, and financial distress, which have a complex impact on financial behavior in the region, particularly in Palopo city,with implications for improving more responsible financial management.